Female hippocampal estrogens have a significant correlation with cyclic fluctuation of hippocampal spines - Kato, Asami (Frontiers Media S.A., 2013)
Synaptic plasticity of the female hippocampus may cyclically fluctuate across the estrous cycle. The spine density fluctuation had been explained by fluctuation of plasma estradiol (E2) and progesterone (PROG), with the assumption that these steroids penetrate into the hippocampus. Recently, however, we demonstrated that male hippocampal levels of sex steroids are much higher than those in plasma, suggesting a weak contribution of plasma steroids to the spine density. By combination of mass-spectrometric analysis with HPLC-purification and picolinoyl-derivatization of hippocampal sex steroids, we determined the accurate concentration of E2 and PROG at four stages of plasma estrous cycle including Proestrus (Pro), Estrus (Est), Diestrus 1 (D1), and Diestrus 2 (D2). Hippocampal levels of E2 and PROG showed cyclic fluctuation with a peak at Pro for E2 and at D1 for PROG, having a positive correlation with the plasma estrous cycle. All these sex steroid levels are much higher in the hippocampus than in plasma. Even after ovariectomy a significant levels of E2 and PROG were observed in the hippocampus. The total spine density showed higher values at Pro and D1, and lower values at Est and D2, having a good correlation with the peak levels of hippocampal E2 or PROG. We also examined fluctuation of the head diameter of spines. Interestingly, mRNA expression level of steroidogenic enzymes (P450arom and 17β-HSD, etc.) and sex-steroid receptors did not significantly change across the estrous cycle. Therefore, the fluctuation of total hippocampal PROG (equal to sum of hippocampus-synthesized PROG and plasma PROG) may be originated from the contribution of cyclic change in plasma PROG, which can induce the fluctuation of total hippocampal E2, since steroid conversion activity of hippocampus might be nearly the same across the estrus cycle.